Properties assessment of laminated oil palm lumber made from super fast dried oil palm wood bonded with different adhesive type and holing alignment - Mohd Nasir, Ruslan (2019)
Malaysia is the largest producer of palm oil in the world and through this activity, it produces huge amount of unutilized Oil palm trunk (OPT). Decreasing of raw material from forest production land, non-wood such as oil palm has become the important alternative raw material. So in this research, OPT is used as an alternative material for wood composite product. After that, the super-fast drying method that has been introduced by Bakar et al. in 2016 can improve the efficiency of drying, and minimize the drying defects. This study was undertaken to determine the gluing condition, holes position and physio-mechanical properties of laminated super-fast dried oil palm lumber. In this study, two different types of adhesive and holes position have been used for produce laminated super-fast dried oil palm lumber. The results revealed that laminated super-fast dried oil palm lumber with optimum physical (thickness swelling and water absorption) and mechanical properties (bending properties and shear strength) was produced using different adhesive and holes position.